1994
DOI: 10.1128/jcm.32.12.2904-2912.1994
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Pneumocystis carinii strains that infect humans based on nucleotide sequence variations of internal transcribed spacers of rRNA genes

Abstract: Small portions of the 18S and the 26S rRNA genes, the entire 5.8S rRNA gene, and internal transcribed spacers ITS1 and ITS2 (located between the 18S and 5.8S rRNA genes and between the 5.8S and 26S rRNA genes, respectively) of Pneumocystis carinii that infect humans were cloned and sequenced. The nucleotide sequences of the 18S, 5.8S, and 26S rRNA genes determined in the study were approximately 90% homologous to those of P. carinii that infect rats, while the sequences of ITS1 and ITS2 of P. carinii from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 33 publications
4
90
1
2
Order By: Relevance
“…With respect to ITS types, the present results revealed a significant diversity in both populations because of the high sequence variability in these genomic regions [17,25,27]. The data suggest a probable dominance of ITS type Eg in the Portuguese population, as reported previously [17], but the second most common ITS type in the Portuguese population was Cg, followed by Gg, which is in contrast to previous findings [17].…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…With respect to ITS types, the present results revealed a significant diversity in both populations because of the high sequence variability in these genomic regions [17,25,27]. The data suggest a probable dominance of ITS type Eg in the Portuguese population, as reported previously [17], but the second most common ITS type in the Portuguese population was Cg, followed by Gg, which is in contrast to previous findings [17].…”
Section: Discussioncontrasting
confidence: 70%
“…Several polymorphic loci have been studied in order to clarify the epidemiological profile of P. jirovecii, with particular respect to its virulence, drug resistance and modes of transmission. The mitochondrial large-subunit rRNA (mtLSU rRNA), the dihydropteroate synthase (DHPS) gene and the internal transcribed spacer regions 1 and 2 (ITS1 and ITS2) of the nuclear rRNA operon are among these loci [12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presented here and in previous reports indicate that three distinct sequevars ofP. carinii exist based on chromosomal rRNA gene sequence and organization: Pcl and Pc2 have been identified in immunosuppressed rats [3,19,201 and Pc3 in multiple human infections [19,21, also see 321. Pcl and Pc2 differ by the absence of a group I intron in the 16s rRNA gene of Pc2 and have distinct sequences for their 26s rRNA introns and 16S, 5.8s and 26s rRNA genes [3,19,20 and Results].…”
Section: Resultssupporting
confidence: 61%
“…The comparison of the introns in the sequence revealed that the rat-derived Pneumocystis rRNA operon contained two group I self-splicing introns, one in the 18S rRNA gene and the other in the 26S rRNA gene, whereas the human-derived organisms only had an intron in the 26S rRNA gene [35]. The internal transcribed spacer (ITS) regions of the nuclear rRNA operon have been used in the analysis of genetic heterogeneity, primarily in isolates of humanderived Pneumocystis [36,37] (see Chapter VI, this volume).…”
Section: Genetic Heterogeneity In Pneumocystis Organisms Isolated Fromentioning
confidence: 99%